Lifestyle scores and their potential to estimate the risk of multiple non-communicable disease-related endpoints: a systematic review - Ding, Jie; Fu, Ruojin; Yuan, Tanwei; Brenner, Hermann; Hoffmeister, Michael (BMC public health, 2025)
Background: Lifestyle scores have emerged as a practical tool to assess the risk of major non-communicable diseases (NCDs). However, most of them are primarily developed for single NCDs. Given the common risk factors for some of the major NCDs, we conducted a systematic review to evaluate the potential of existing lifestyle scores in predicting the risk of multiple NCD-related endpoints. Methods: PubMed, Web of Science, the Cochrane Library, Embase, and Google Scholar were searched from inception to October 2024. We included observational studies assessing the association between lifestyle scores and the risk of morbidity or mortality of multiple NCDs, including type 2 diabetes (T2D), cardiovascular disease (CVD), and cancer. Results: Of 16,138 unique records identified by the search, 56 eligible studies were included in the systematic review, consisting of 48 cohort studies, 5 case-control studies, 2 case-cohort studies, and 1 cross-sectional study from 16 countries. 15 lifestyle scores were identified to estimate the risk of 32 NCDs, with HLIBMI being the most reported score (14/56, 25.0%). Moderate to strong associations were found between the 15 lifestyle scores and the risk of developing and dying from multiple types of cancers, CVDs, and T2D. Healthy lifestyle scores including additional risk factors (i.e., blood pressure, blood glucose, and waist circumference) aside from major risk factors (i.e., Body Mass Index (BMI), smoking, and diet) seemed to have a stronger ability to estimate NCDs risk than scores including only major risk factors. Conclusion: All 15 simple lifestyle scores were shown to estimate the risk of multiple NCDs endpoints, although some scores were originally developed to estimate the risk of single diseases only. Therefore, further research is required to identify which lifestyle score is most effective for assessing the risk of multiple NCD-related endpoints in a head-to-head comparison.
Gesehen am 27.08.2025